OUTDOOR LEARNING-BASED THEMATIC LEARNING - Yulia Karlina; Rochmiyati Rochmiyati; Dwi Yulianti (Teunuleh Publisher, 2021)
This research is a research on developing a test instrument for higher-order thinking skills based on outdoor learning for fifth grade elementary school students. This study aims to 1) develop a test instrument for higher order thinking skills based on outdoor learning in elementary schools; 2) validate the test instrument through expert validation and empirical validity. Expert validation is carried out by consulting the product development design with expert lecturers. Empirical validity was carried out using the product moment correlation formula, while the determination of reliability used the Cronbach Alpha formula. The research method uses Design Based Research. The development of this model is carried out in stages 1) identification and problem analysis by researchers and practitioners collaboratively 2) developing solutions based on theoretical benchmarks, existing design principles and technological innovations 3) carrying out an iterative process to test and improve practical solutions 4) reflection to produce design principles and improve implementation of practical solutions. The results of the study are 1) 22 items of higher order thinking skills; 2) validation by experts states that this assessment instrument is suitable for use as an assessment tool, while in empirical validation it is stated that the overall results of the test using the product moment formula of the items have been declared valid. Determination of reliability using Cronbach's alpha formula has a reliability value of 0.935 which is categorized as high reliable. Overall, in this development research, this higher-order thinking ability assessment instrument is valid and reliable as a form of assessment.